Enhanced ionic liquid mobility induced by confinement in 1D CNT membranes. Issue 15 (29th March 2016) - Berrod, Q.; Ferdeghini, F.; Judeinstein, P.; Genevaz, N.; Ramos, R.; Fournier, A.; Dijon, J.; Ollivier, J.; Rols, S.; Yu, D.; Mole, R. A.; Zanotti, J.-M.
Abstract : Ionic liquids confined in vertically aligned carbon nanotubes membrane exhibit an enhanced mobility. This could lead to high power batteries separators. Abstract : Water confined within carbon nanotubes (CNT) exhibits tremendous enhanced transport properties. Here, we extend this result to ionic liquids (IL) confined in vertically aligned CNT membranes. Under confinement, the IL self-diffusion coefficient is increased by a factor 3 compared to its bulk reference. This could lead to high power battery separators.